Do Corporate Social Responsibility and Corporate Governance Affect Tax Aggressiveness? Evidence from Indonesia - Hasibuan, David H.M.; ., Khomsiyah (Journal of Accounting, Business and Finance Research, 2019)
For businesses in Indonesia, corporate social responsibility (CSR) is still seen as an additional burden that will incriminate the company. Based on the observations of two companies that received awards for the CSR programs, it seems that the company always received a Tax Underpayment Assessment Letter (SKPB) from the Directorate General of Taxes for the period 2014-2017. This suggests that the burden of CSR incurred by the company exceeds the limits set out in the provisions of Minister of Finance Regulation No. 76/PMK.03 (2011). The indications that arise for these conditions are the efforts made by the company to practice tax avoidance by posting CSR expenses above the applicable provisions with the aim of reducing corporate’s income taxes. But the aggressive tax planning measures should be minimized by implementation of good corporate governance (GCG). This study aims to examine the effect of CSR and corporate governance (CG) on corporate tax aggressiveness and the effect of CSR on tax aggressiveness which is moderated by corporate governance. The objects of the research are the financial statements of public companies listed on the Indonesia Stock Exchange (IDX) with the observation period of 2014– 2017. The data are analysed using multiple linear regression. The test results show that CSR has a positive effect on tax aggressiveness, however corporate governance does not affect tax aggressiveness. Furthermore, corporate governance has no effect in moderating the effect of CSR on tax aggressiveness.